Construction dispute research : conceptualisation, avoidance and resolution - Cheung, Sai On, editor. (New York : Springer, 2014)
There are three specific purposes of this book. First, this volume aims to summarise studies on construction dispute. Second, apart from the theoretical constructs, where appropriate empirical tests are also included. This approach serves to go beyond the commonly used anecdotal approach for the subject matters. Third, it is the sincere hope of the authors that this book will help shaping research agenda of construction dispute. The studies are mostly framed from a management perspective drawing on methods and concepts in contract law, economics, psychology and management science. The studies presented in this book collectively demonstrate holistic approach in dispute management. Each chapter can be read as a study on its own. Practitioners will find the book a handy reference in dispute management and resolution. Students would find the book useful in explaining in details the causes of dispute, the processes to resolve them. The research design and empirical approaches are particularly useful to students in construction management, architectural, surveying and civil engineering programs. --